The effect of phase parameter variation on hardness of P91 components after service exposures at 530–550 °C. (15th January 2018) - Peng, Z.F.; Liu, S.; Yang, C.; Chen, F.Y.; Peng, F.F.
Abstract: As a significant property index required by the related ASME and ASTM codes, hardness values of some P91 heat resistant steel components have been evidently reduced after a relatively short term (tens of thousands of hours) of service exposures in quite a number of thermo-power generation sets, leading to a worldwide concern in the related fields. Through the application of SEM-EDS+MPST technology and data-fittings, functions are established to quantitatively reveal the weighted relationships of total amount of carbon in matrix ( P C-matrx ) and hardness value (HV0.1) with volume fractions and equivalent diameters of M23 C6 carbides and Laves phase ( V M23C6, V Laves d M23C6 and d Laves ) for the P91 components after service exposures at 530–550 °C and 3.53–17.4 MPa for 57, 000–63, 000 h, respectively. An excessive increase in V M23C6 and d M23C6 resulted in matrix softening with carbon-depletion of martensite and formation of ferrite (abnormal microstructure) due to an insufficient heat treatment after uneven thermoforming while a relatively large increase/decrease in V Laves / d Laves of Laves phase (normal microstructure) could effectively inhibit further precipitation and coarsening of M23 C6 and hence keep the matrix relatively strong in the service exposure duration investigated. The relevant causes of forming the abnormal microstructures and the precipitate coarsening mechanism associated with Cr content in M23 C6 carbides ( C Cr-M23C6 ) and Fe/Cr ratio in Laves phase ( C Fe-Laves / C Cr-Laves ) were analyzed. The elemental exchanges of Cr, Mo and Si between phases and the interactions between precipitates and boundaries were also discussed. The quantitative relationship and the related mechanism can be used as reference for microstructure and property degradation assessments of service exposed P91 components. Graphical abstract: Image 1